Effect of the method of photopolymerization of dental composites based on dimethacrylate resin on the shrinkage stresses and selected properties of the cured material - Bociong, K.; Krasowski, M.; Domarecka, M.; Sokołowski, J. (Polimery, 2021)
The composite materials used in conservative dentistry were obtained through polymerization of dimethacrylate resins by light with different power density. The effects of composite irradiation method on the shrinkage stresses induced in the material and selected properties of the cured product were analyzed. The polymerization was carried out for 60 s irradiating the sample from one side continuously, intermittently (after every 20 sec exposure the samples were conditioned for 5 min), by using the "soft-start” method (10s at 200 mW/cm2, 5 s at 200–1400 mW/cm2, remaining time at 1400 mW/cm2) or "pulse delay” method (2 s at 200mW/cm2, 2 min break, 58 s at 1400 mW/cm2). The efficiency of polymerization, diametral tensile strength (DTS) and Vickers microhardness (HV) of the composites were evaluated. It was found that the smallest stresses are generated during the irradiation of the composite in aconventional way (continuous exposure) and using "pulse delay” method. The largest stresses occur in the material irradiated in an intermittent way. The composite irradiated using "pulse delay” method has the highest hardness HV1. There are no statistically significant differences between DTS of the differently polymerized samples. Regardless of how long and by what method the composites were cured their degree of conversion was satisfactory and not lower than 65%.